SmartPower technology for the formation of martial arts shok actions - Stepanov, M. Y.; Salamatov, M. B. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to substantiation of the effectiveness of SmartPower technology in percussion martial arts. Methods and structure of the study. SmartPower technology is based on load analysis, manifested in the form of vector forces. Its main task is to develop the power of sports movement through a system of exercises. The innovative technology of forming vector forces is based on an information database obtained using a computer program from the inertialess simulator KIT-70, trackers HYKSO, BIODEX, dynamic bag Kicktest-100. To evaluate the effectiveness of the technology, an experiment was conducted in the city of Chaikovsky on the basis of USK "Burevestnik". The participants were 38 thaiboxers aged 14-15, divided into two equal groups CG and EG, 19 athletes in each. The EG studied according to the proposed technology, the CG according to the program for the Youth Sports School. Results and conclusions. Training in the EG under the control of exercises that maximally simulate shock actions using KIT-70 contributed to significantly significant changes in all the studied parameters. The technology, built on interconnected sets of exercises with an optimal effect on the vector effort, will allow achieving the planned sports result not only in martial arts, but also in other speed-strength sports.